2020
DOI: 10.1177/0898010120938558
|View full text |Cite|
|
Sign up to set email alerts
|

Teaching Guided Imagery and Relaxation Techniques in Undergraduate Nursing Education

Abstract: Guided imagery and relaxation techniques have many documented benefits yet are not traditionally taught in undergraduate nursing education. These techniques can also be used by clinicians and students to manage their own stress. The impact of teaching guided imagery in an experiential skills lab on undergraduate nursing students was examined in this mixed-methods research study. Goals were to evaluate whether students learning these skills would be more likely to use them in clinical practice, to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…It's subsequently reflected in increase students' satisfaction with mental imagery as a method of teaching. Windle (2020) [28] who was in the same line with finding of the present study and reported that nursing students were satisfied with guided imagery teaching experience and it is achieved valuable personal and professional benefits.…”
Section: Discussionsupporting
confidence: 86%
“…It's subsequently reflected in increase students' satisfaction with mental imagery as a method of teaching. Windle (2020) [28] who was in the same line with finding of the present study and reported that nursing students were satisfied with guided imagery teaching experience and it is achieved valuable personal and professional benefits.…”
Section: Discussionsupporting
confidence: 86%
“…As future professionals, students not only need to have professional skills, but also need to have a high sense of social responsibility and professional ethics. Vocational undergraduate education needs to integrate the cultivation of social responsibility into the education process, so that students can pay attention to social issues in learning and practice, actively participate in social welfare activities and make contributions to society [10] .…”
Section: The Need For Social Developmentmentioning
confidence: 99%